Review on software metrics thresholds for object-oriented software - Bakar, Abubakar Diwani; Md Sultan, Abu Bakar; Zulzalil, Hazura; Din, Jamilah (Praise Worthy Prize, 2013)
Software metrics like any other measures have been advocated as the essential tool in Object-oriented systems. Controlling software metrics is an important for building quality software systems. Software metrics thresholds have been used in various disciplines in identifying the unsafe design by setting an alarm at a place where the value of the specific internal measure exceeds some predefined values. Although, the researchers and other practitioners tried to introduce a variety of software metrics, but the issue of thresholds has been given limited attention. A few meaningful software metric thresholds have been introduced in the literature. In this review paper, the authors went through different literatures to identify the existing object-oriented software metrics thresholds in order to gain an insight about the phenomena. By studying the validation process and the sensations of the metrics presented in the literature, the study found the thresholds for CK metrics have been validated more than any other metrics.